Abortion experience and self-efficacy: exploring socioeconomic profiles of GHANAIAN women - Lambon-Quayefio, M.P.; Owoo, N.S.; Onuoha, N. (BMC Reproductive health, 2019)
Background: Unsafe abortions remain a major global public health concern and despite its prevalence, unsafe abortions remain one of the most neglected global health challenges. The proportion of women in Ghana who have experienced unsafe abortions has increased from 45% in 2007 to 62% in 2017. Given the noted consequences of (unsafe) abortions on women health, it is important to explore factors correlated with women’s abortion decisions and why they opt for safe or unsafe methods. The study also examines determinants of over 6,000 Ghanaian women’s selfefficacy in abortion decision-making, given that this is likely to affect the likelihood of future abortions. Methods: Using cluster-level Geographic Information System data from the 2017 Ghana Maternal Health Survey, the study provides a hot spot analysis of the incidence of abortion in the country. The study also makes use of Probit multivariate analyses also show the correlates of abortion with socio-economic factors. Results: Results suggest that abortion among women is positively correlated with the absence of partners, low education levels, higher household wealth, lower parity and family size, polygyny and Christian religious background. Conclusion: It is observed that the groups of women with higher abortion self-efficacy are the same groups of women who are more likely to opt for safer abortion methods, indicating some correlation, albeit indirect, between abortion self-efficacy and women’s abortion behaviors in Ghana. Relevant policy applications are adduced from these research findings.
Research Article
Keywords: Abortion; Self-efficacy; Spatial hot spots; GIS; Ghana maternal health survey